Determining the level of knowledge regarding effective wound cleaning among nurses aged 22 years and above working at Rakai General Hospital, Rakai District. A cross-sectional study. - Namawejje, Esther; Nansereko, Hasifah; Naggulu, Immaculate; Nalubega, Jane Frank (Student's Journal of Health Research Africa, 2026)
Background Wound cleaning is a critical component of wound care that involves the removal of dead tissue, dirt, bacteria, and other contaminants to prevent infection and promote healing. The purpose of this study was to assess the knowledge of nurses aged 22 years and above regarding effective wound cleaning at Rakai General Hospital, Rakai District. Methods A descriptive cross-sectional study design employing a quantitative research method was used to collect data from 32 nurses at Rakai General Hospital who were sampled using a purposive sampling technique within a period of 3 days. Data was collected with a structured questionnaire, coded, analyzed using Microsoft Excel (2019) programs, and findings were presented in frequency tables, graphs, and pie-charts. Results Out of 32 respondents sampled, 20(62.5%) were females. 16(50%) of the respondents reported patient loads as a hindrance to effective cleaning of a wound, while a few 6(18.75%) mentioned limited supervision. Knowing how to use antiseptics was identified by 15(46.9%) of respondents as a factor that made wound cleaning safer, while frequent exposure to complex wounds was mentioned by 5(15.6%). 18(56.3%) indicated that regular in-service training plays a major role, whereas hospital rules were recognized by a minimal number of 5(15.6%). 22(68.75%) reported that workshops contribute significantly to improving knowledge, while infection team talks were mentioned by only 6.25% (n=2), making it the least selected option. Conclusion Although many nurses understood basic wound-care principles such as the use of saline, hand hygiene, and antiseptic application, gaps still existed due to high patient loads, limited documentation, and inconsistent refresher training. Recommendation The Management should provide regular in-service training and workshops focused on wound-care guidelines, aseptic techniques, and documentation skills to improve nurse competence and consistency.